2015
DOI: 10.1186/s13075-015-0764-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum calprotectin (S100A8/9): an independent predictor of ultrasound synovitis in patients with rheumatoid arthritis

Abstract: IntroductionCalprotectin, a heterodimeric complex of S100A8/9 (MRP8/14), has been proposed as an important serum biomarker that reflects disease activity and structural joint damage in rheumatoid arthritis (RA). The objective of this cross-sectional study was to test the hypothesis that calprotectin is associated with clinical and ultrasound-determined disease activity in patients with RA.MethodsA total of 37 patients with RA (including 24 females, a mean disease duration of 20 months) underwent a clinical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
(41 reference statements)
5
50
0
3
Order By: Relevance
“…The ultrasonographers were blinded to each patient’s clinical examination and laboratory findings. The inter- and intra-observer reliability was moderate to very good, as shown in a recent study [27]. …”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…The ultrasonographers were blinded to each patient’s clinical examination and laboratory findings. The inter- and intra-observer reliability was moderate to very good, as shown in a recent study [27]. …”
Section: Methodssupporting
confidence: 61%
“…Recently, we demonstrated an association between serum calprotectin and clinical and laboratory markers of disease activity and, more relevantly, with ultrasound synovitis, which is generally considered to be more precise in the evaluation of joint inflammation [27]. Moreover, we found that serum calprotectin might be a better predictor of ultrasound-determined synovitis than CRP [27].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In rheumatoid arthritis, it increases during the acute phase of the disease, decreases after treatment, and is more sensitive than the hepatic-originated classic acute phase proteins (11)(12). In AITD, which is also associated with inflammation, serum S100A8/S100A9 levels have not yet been determined.…”
mentioning
confidence: 99%
“…Calprotectin derives predominantly from neutrophils and monocytes and was previously reported to be associated with structural joint damage in psoriatic arthritis (PsA) and RA [45]. Jana Hurnakova and Colleagues investigated serum calprotectin levels in 37 patients with RA [46] and reported that calprotectin levels significantly correlate with DAS28 (r=0.385, p<0.05), CRP (r=0.629, p<0.001), and swollen joint count (r=0.465, p<0.005). In addition, calprotectin is significantly associated with the findings in gray-scale and power A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 92%